Analisis Kemampuan Pemecahan Masalah dengan Model Pembelajaran Problem Based Learning di SMP Negeri 4 Gunungsitoli Selatan - Ester Primajuni Zebua; Netti Kariani Mendrofa (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to present information and also find out about students' problem-solving skills using Problem Based Learning methods and methods conducted at SMP Negeri 4 Gunungsitoli Selatan. The design of this study used the Quasi-Experimental method with the pretest-posttest control group design method. The sample for this study was about 40 respondents, of which 20 students were in class I or experiment I. Meanwhile, 20 students were in class 2 or experiment II. From the research results obtained, the results of the t test were obtained with a calculated t value which had a value of 4,977. Meanwhile, the t table value at α is 0.05 and dk: 38 has a value of 1.6860. Thus t count has a greater value than t table, namely 4,977 ˃ 1,686). With this result, H0 is rejected and the H1 hypothesis is accepted. From these results it was found that there were significant results between students' problem solving abilities towards problem solving by applying the problem based learning learning model.